Energy-saving and consumption-reducing method for electrolytic manganese metal
By installing multi-layer insulation and thermal insulation materials outside the electrolytic cell, the electrode material and temperature control are improved, and the problems of high current loss and energy consumption in the electrolytic manganese metal are solved, thereby achieving a safe and efficient electrolytic process.
Patent Information
- Application Number
- CN202411396060.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-21
AI Technical Summary
During the electrolytic process of manganese metal, the current loss is large due to the lack of insulation of the electrolytic cell. The current is needed to increase the current for electrolysis, resulting in uncontrollable current overflow, resulting in current leakage and electric shock accidents, and increasing energy consumption.
By installing multiple layers of insulating materials and heat insulating materials outside the electrolytic cell, insulating and insulating treatments will increase the conductivity and catalytic activity of the electrode material, and maintain the electrolyte temperature at 35-40 degrees Celsius through a temperature control device.
Effectively prevent current leakage, reduce energy consumption, improve electrolytic efficiency, ensure operational safety, extend the service life of the electrode, and reduce production costs.
Smart Images

Figure CN119491271A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolysis of electrolytic manganese metal, in particular to an energy-saving and consumption-reducing method for electrolytic manganese metal. Background Art
[0002] Electrolytic manganese metal is a common process in industrial production, used to extract pure manganese metal from manganese ore. This process usually takes place in an electrolytic cell, and the electrolyte contains dissolved manganese. Under the action of electric current, the manganese ions in the manganese ore are reduced to metallic manganese, which is deposited on the cathode. This method makes the extraction and refining of manganese more efficient and controllable. Electrolytic manganese metal requires a lot of electricity as a driving force, and electricity consumption accounts for a significant part of the production cost. Therefore, through energy-saving measures, production costs can be reduced and economic benefits can be improved.
[0003] However, during the electrolysis of most metallic manganese, the current loss is large because the electrolytic cell is not insulated, so it is necessary to increase the current for electrolysis. As a result, the current overflow during electrolysis is uncontrollable, resulting in a large amount of current leakage, causing operators to touch live parts and get electric shock accidents, and current loss, thereby increasing energy consumption. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides an energy-saving and consumption-reducing method for electrolytic manganese metal, which solves the problems of a large amount of current leakage causing operators to touch live parts and causing electric shock accidents, and current loss resulting in increased energy consumption.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] 1. A method for energy saving and consumption reduction of electrolytic manganese metal, comprising the following steps:
[0007] S1. Insulation and heat insulation treatment of the electrolytic cell: multiple layers of insulating materials are arranged outside the electrolytic cell, and heat insulation materials are arranged outside the insulating materials. The insulating materials and the tops of the heat insulation materials are provided with openings for the electrolytic cell to slide into the inside;
[0008] S2: Selecting metallic manganese: First, check whether the purity of metallic manganese meets the standard; second, observe whether the surface of metallic manganese has uniform color; third, select metallic manganese with complete particle size and shape, and then add the selected metallic manganese into the electrolytic cell;
[0009] S3: Adding additives: When adding a certain surfactant as an additive to the electrolytic copper cell, first dissolve it in deionized water to prepare a solution of a certain concentration, then add the solution to the electrolyte at a stable flow rate through evenly distributed nozzles installed on the upper part of the electrolytic cell, observe the change in the copper deposition quality, and add additives to the inside of the electrolytic cell, the additives including selenium dioxide, sulfite ions and gelatin;
[0010] S4: Replacement of electrode materials: Before replacement, first stop the operation of the electrolytic cell and cut off the power supply, empty and clean the electrolyte in the electrolytic cell, and thoroughly clean the electrolytic cell to remove residual electrolyte and sediment, remove the old electrode and the wires, clamps or fixtures connected to the old electrode, and gradually remove the old electrode. The electrode material anode includes a titanium-based coated anode or a lead alloy anode, the cathode material includes a stainless steel cathode or a pure copper cathode, and the diaphragm material is an asbestos diaphragm or an ion exchange membrane;
[0011] S5: Waste heat recovery: The electrolyte temperature is maintained at 35-45 degrees Celsius by means of a temperature recovery device, wherein the temperature recovery device includes a heat exchanger or a heat pump;
[0012] S6: Control temperature: When controlling the temperature, first stop the operation of the electrolytic cell and cut off the power supply. The first step is to detect the temperature of the electrolyte. When it exceeds 45 degrees Celsius, a temperature control device is used to cool it down. When it is lower than 30 degrees Celsius, a temperature control device is used to heat it up. When testing the temperature, the temperature control device includes an air-cooled heat exchanger and an electric heater.
[0013] Preferably, in S1, the insulating material is provided in multiple layers, and the insulating material includes ceramic or glass fiber reinforced plastic FRP, rubber or polytetrafluoroethylene PTFE, the thickness of the ceramic is 3-5mm, the thickness of the glass fiber reinforced plastic is 3-5mm, the thickness of the rubber is 5-7mm, and the thickness of the polytetrafluoroethylene PTFE is 5-7mm.
[0014] Preferably, in S1, the thermal insulation material comprises aluminum silicate fiber or aerogel thermal insulation material, the thickness of the aluminum silicate fiber is 3-5 mm, and the thickness of the aerogel thermal insulation material is 3-5 mm.
[0015] Preferably, S2: Selecting metallic manganese: Testing the purity index of metallic manganese. Its purity can be confirmed through relevant test reports or certificates. The surface of metallic manganese should be uniform in color, without obvious oxidation, rust, cracks or other defects. If there are specific requirements for particle size and shape, check whether it meets the standards.
[0016] Preferably, in S2, the amounts of the additives are 2-4 parts of selenium dioxide, 1-3 parts of sulfite ions, and 5-15 parts of gelatin.
[0017] Preferably, in S4, the thickness of the electrode material is 0.5-0.8 mm for a titanium-based coated anode or 0.5-0.8 mm for a lead alloy anode, the thickness of the cathode material is 0.5-0.8 mm for a stainless steel cathode or 0.5-0.8 mm for a pure copper cathode, and the thickness of the diaphragm material is 1-2 mm for an asbestos diaphragm or 1.5-2.5 mm for an ion exchange membrane.
[0018] Preferably, in S5: the temperature control device adopts a heat exchanger or a heat pump, and when the electrolyte flows out of the tank, the temperature is absorbed and converted by the heat exchanger or the heat pump, and the electrolyte temperature is maintained at 35-40 degrees Celsius by the heat exchanger or the heat pump.
[0019] Preferably, in S6: the temperature control device adopts an air-cooled heat exchanger and an electric heater. When the temperature of the electrolyte in the pipeline exceeds 40 degrees Celsius, the air-cooled heat exchanger is started, with an air flow rate of 13500-27000 per minute. When the temperature of the electrolyte in the pipeline is lower than 35 degrees Celsius, the electric heater is started, and the temperature is set to 70-80 degrees Celsius for heating for two minutes. When the temperature is heated to 20-30 degrees Celsius, the temperature of the heater is set to 40-45 degrees Celsius, and the temperature is waited for to rise.
[0020] The present invention provides an energy-saving and consumption-reducing method for electrolyzing manganese metal, which has the following beneficial effects:
[0021] 1. The present invention effectively prevents the current in the electrolytic cell from leaking to the outside by insulating and heat-isolating the electrolytic cell, avoids electric shock accidents caused by operators contacting live parts, and ensures the safety of the working environment. Good insulation can reduce the loss of current and concentrate more electric energy on the electrolytic reaction, thereby improving the electrolytic efficiency and reducing energy consumption. The heat-insulating material can avoid the loss of temperature during the electrolysis process and reduce the energy consumption when maintaining the temperature.
[0022] 2. The present invention has better conductivity and catalytic activity by replacing the electrode material, which can accelerate the electrolysis reaction, improve current efficiency and production efficiency, improve product quality, help obtain purer, better crystallized, and better physically performing electrolysis products, enhance product competitiveness in the market, enhance corrosion resistance, extend the service life of the electrode, reduce frequent replacement due to electrode corrosion, reduce production costs and maintenance workload, and reduce energy consumption. Efficient electrode materials can reduce electricity consumption under the same electrolysis conditions, achieve energy conservation and emission reduction, and reduce production costs.
[0023] 3. The present invention has concluded through experimental research that when the electrolyte temperature is controlled at 35-40 degrees Celsius, the electrolysis efficiency is the highest and the energy consumption is relatively low, which can make the ion migration speed in the electrolysis reaction, the reaction rate on the electrode surface, etc. reach the optimal state. When electrolyzing metallic manganese, controlling the temperature at 35-40 degrees Celsius can make the deposited manganese layer denser and the impurity content lower, reduce side reactions and avoid unnecessary side reactions caused by excessively high or low temperatures. At 35-40 degrees Celsius, the life of the equipment can be extended. A stable and suitable temperature can reduce the thermal stress of the electrolytic cell and related components, reduce the corrosion and aging rate of the equipment, and reduce the maintenance and replacement costs. By controlling the temperature at 35-40 degrees Celsius, the current efficiency is successfully increased from 85% to 92%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] The embodiment of the present invention provides a method for energy saving and consumption reduction of electrolytic manganese metal, comprising the following steps:
[0028] S1. Insulation and heat insulation treatment of the electrolytic cell: multiple layers of insulating materials are arranged outside the electrolytic cell, and heat insulation materials are arranged outside the insulating materials. Openings are opened on the tops of the insulating materials and the heat insulation materials to allow the electrolytic cell to slide into the inside;
[0029] S2: Selecting metallic manganese: First, check whether the purity of metallic manganese meets the standard; second, observe whether the surface of metallic manganese has uniform color; third, select metallic manganese with complete particle size and shape, and then add the selected metallic manganese into the electrolytic cell;
[0030] S3: Adding additives: When adding a certain surfactant as an additive to the electrolytic copper cell, first dissolve it in deionized water to prepare a solution of a certain concentration, then add the solution to the electrolyte at a steady flow rate through evenly distributed nozzles installed on the upper part of the electrolytic cell, and observe the change in the copper deposition quality, and add additives to the inside of the electrolytic cell, the additives include selenium dioxide, sulfite ions and gelatin;
[0031] S4: Replacement of electrode materials: Before replacement, first stop the operation of the electrolytic cell and cut off the power supply, empty and clean the electrolyte in the electrolytic cell, and thoroughly clean the electrolytic cell to remove residual electrolyte and sediment, remove the old electrode and the wires, clamps or fixtures connected to the old electrode, and gradually remove the old electrode. The electrode material anode includes titanium-based coated anode or, the cathode material includes stainless steel cathode, and the diaphragm material is asbestos diaphragm;
[0032] S5: Waste heat recovery: The electrolyte temperature is maintained at 35-45 degrees Celsius by means of a temperature recovery device, which includes a heat exchanger;
[0033] S6: Control temperature: When controlling the temperature, first stop the operation of the electrolytic cell and cut off the power supply. The first step is to detect the temperature of the electrolyte. When it exceeds 45 degrees Celsius, a temperature control device is used to cool it down. When it is below 30 degrees Celsius, a temperature control device is used to heat it up. When testing the temperature, the temperature control device includes an air-cooled heat exchanger.
[0034] In S1, the insulating material is provided with multiple layers, and the insulating material includes ceramic and rubber, the thickness of the ceramic is 3 mm, and the thickness of the rubber is 5 mm;
[0035] The 3mm ceramic is used as the insulating liner. The ceramic itself has good insulation performance, high temperature resistance and chemical stability during use, which can avoid penetration and pollution caused by electrolyte corrosion during the electrolysis process. The second layer is paved with 5mm rubber. The rubber has certain elasticity and flexibility, which can adapt to some special shapes and parts of the electrolytic cell and provide good insulation effect. The electrolysis process usually involves high voltage and high current. If the electrolytic cell is not insulated, the current may leak to the outside, causing electric shock to the operator. The electrolytic cell insulation also has the effect of enhancing the insulation performance of the electrolytic cell and preventing energy loss caused by current leakage, thereby achieving the effect of energy saving and reducing losses;
[0036] In S1, the thermal insulation material includes aluminum silicate fiber, and the thickness of the aluminum silicate fiber is 3 mm;
[0037] Aluminum silicate fiber has low thermal conductivity, which can effectively prevent the heat in the electrolytic cell from dissipating outward, maintain a stable working temperature, and reduce energy consumption. Its high temperature resistance allows it to work stably for a long time in a high temperature environment and adapt to the high temperature that may be generated during the electrolysis process. Its good chemical stability can resist the erosion of chemical substances in the electrolyte, and it is not easy to react chemically, ensuring the durability of its performance. Low thermal conductivity helps to reduce the heat exchange between the electrolytic cell and the outside world, improve the electrolysis efficiency, and reduce production costs. In the experiment, after the electrolytic cell was insulated with aluminum silicate fiber, the surface temperature of the electrolytic cell was significantly reduced, reducing heat loss, and the electrolysis efficiency was also improved. After a long period of operation, the aluminum silicate fiber still maintains good performance, does not need to be replaced frequently, and reduces maintenance costs;
[0038] In S2: first, check whether the purity of the manganese metal meets the standard; second, observe whether the surface of the manganese metal has uniform color; third, select the manganese metal with complete particle size and shape, and then add the selected manganese metal into the electrolytic cell;
[0039] Purity Understand the purity index of manganese metal. High-purity manganese metal usually performs better in some applications with high quality requirements. Its purity can be confirmed by relevant test reports or certificates. Manganese metal ore with deviation in purity cannot obtain relative purity after electrolysis, which will cause economic losses. The surface of manganese metal should be uniform in color, without obvious oxidation, rust, cracks or other defects. Manganese metal with smooth and flat surface is usually of better quality and has higher purity after electrolysis. Particle size and shape If there are specific requirements for particle size and shape, check whether it meets the standards. Manganese metal with specific particle size and shape can provide a larger reaction surface area, accelerate the reaction rate, and increase the reaction rate. Good particle size and shape are conducive to subsequent processing technology, such as forming, forging, welding, etc., to improve the accuracy and quality of processing and reduce losses and defects during processing;
[0040] In S3, the additives are 2 parts of selenium dioxide, which can improve the structure and appearance of cathode deposits and reduce the formation of dendrites during the experiment; 1 part of sulfite ions, which can improve the electrolysis efficiency and quality of manganese metal during the experiment; and 5 parts of gelatin, which can refine crystals and make cathode deposits more uniform during the experiment;
[0041] In S4, the thickness of the electrode material is 0.5mm for the titanium-based coating anode, the cathode material includes a stainless steel cathode of 0.5mm, and the thickness of the diaphragm material is an asbestos diaphragm of 1mm;
[0042] During the experiment, the titanium-based coated anode improved its corrosion resistance and effectively resisted the erosion of the electrolyte, extended the service life of the anode, reduced the cost and downtime of frequent replacement due to anode corrosion, and reduced the anode potential, which helped to reduce the energy consumption in the electrolysis process and improve the efficiency of electric energy utilization, thereby reducing production costs, reducing the generation of byproducts such as oxygen inhibited by side reactions, and improving the selectivity of the electrolysis reaction, so that more current can be used for manganese deposition, improving the current efficiency and optimizing the charge transfer in the electrolysis process, so that the current can be more effectively used for the precipitation of metallic manganese, and improving the current efficiency. Improve the stability of the electrolytic cell Due to its good electrochemical properties and stability, it can reduce fluctuations in the electrolysis process and ensure the stability of electrolytic production. After using the titanium-based coated anode in the experiment, the service life of the anode was extended from several months to more than one year, and the current efficiency was increased by about 8%, which significantly reduced the production cost and improved the stability of product quality. It successfully reduced the amount of oxygen precipitation, so that more electric energy can be used for manganese deposition, and the power consumption per ton of metallic manganese was reduced by about 500 degrees;
[0043] Stainless steel has good electrical conductivity. The use of stainless steel cathode can ensure uniform current distribution, which is conducive to the deposition of metal manganese on the cathode and improves electrolysis efficiency. The corrosion resistance can resist the corrosion of the electrolyte, extend the service life of the cathode, reduce equipment maintenance costs and replacement frequency, and the surface flatness usually has a relatively flat surface, which helps to obtain a uniform, dense and flat metal manganese deposition layer, improve product quality, and cost-effectiveness. Compared with some special expensive cathode materials, stainless steel is relatively economical in cost and can meet the basic requirements of electrolysis of metal manganese. In the experiment, after the use of stainless steel cathode for electrolysis of manganese, the service life of the cathode was extended by 30% compared with the ordinary metal cathode used before, reducing production interruptions caused by cathode replacement. Due to the good conductivity of the stainless steel cathode, the current efficiency was increased by 5%. At the same time, its flat surface makes the quality of the metal manganese deposit more uniform and reduces the production of defective products.
[0044] Ion-selective permeation of asbestos diaphragm can allow specific ions (such as manganese ions) to pass through, while preventing the migration of some impurity ions, which helps to improve the purity of electrolysis products, separate the anode and cathode regions, effectively separate the anode and cathode regions of the electrolytic cell, prevent the direct mixing of the anode and cathode electrolytes, and ensure the normal progress of the electrolysis reaction. Maintaining the electrolyte concentration difference helps to maintain the concentration difference of the electrolyte on both sides of the anode and cathode, thereby forming a certain electrochemical driving force and promoting the progress of the electrolysis reaction. The cost is relatively low. Compared with some new high-performance diaphragm materials, the cost of asbestos diaphragm is relatively low and suitable for large-scale industrial production applications. After using asbestos diaphragm in the experiment, the deposition of impurities on the cathode was successfully reduced, and the purity of metallic manganese was increased from 98% to more than 99%. The use of asbestos diaphragm to separate the anode and cathode regions stabilizes the electrolysis process, improves production efficiency, and reduces production costs;
[0045] In S5: the temperature control device adopts a heat exchanger, and when the electrolyte flows out of the tank, the temperature is absorbed and converted by the heat exchanger or heat pump, and the electrolyte temperature is maintained at 35-40 degrees Celsius by the heat exchanger or heat pump;
[0046] Experimental research shows that when the electrolyte temperature is controlled at 35-40 degrees Celsius through a heat exchanger, the electrolysis efficiency is the highest, the energy consumption is relatively low, and the current efficiency is improved. Within this temperature range, the migration speed of ions is more suitable, which can reduce the loss of electric energy and improve the utilization efficiency of current in the electrolysis process. During electrolysis, the cathode deposition quality can be improved, which helps to form a more uniform, dense and flat cathode deposition, reduce crystal defects and impurity inclusions, thereby improving the purity and quality of metallic manganese. The current efficiency has been increased by about 5%, and the quality of the cathode deposition has been significantly improved, and the qualified rate of the product has been greatly improved. The energy consumption per ton of manganese metal production has been greatly improved, and the energy consumption per ton of manganese metal production has been reduced by about 10%. During use, the current output power can be reduced, so as to achieve the standard heat exchanger before the improvement. The plate heat exchanger or the tube heat exchanger is used to recycle the high-temperature fluid discharged from the electrolytic cell and the low-temperature fluid that needs to be heated. When in use, the electrolyte flowing out of the electrolytic cell can avoid a large temperature loss, so that the electrolyte maintains the temperature, reduces the power consumption of the heater, improves the electrolysis of manganese metal at a constant temperature during use, maintains the consistency of the electrolyte temperature, and improves the consistency of manganese metal batches during production;
[0047] In S6: the temperature control device uses an air-cooled heat exchanger and an electric heater. When the temperature of the electrolyte in the pipeline exceeds 40 degrees Celsius, the air-cooled heat exchanger is started, and the air flow rate is 13500 per minute. When the temperature of the electrolyte in the pipeline is lower than 35 degrees Celsius, the air-cooled heat exchanger is started, and the temperature is set to 70 degrees Celsius for two minutes. When the temperature is heated to 20 degrees Celsius, the temperature of the heater is set to 45 degrees Celsius, and the temperature is waited for to rise;
[0048] The air-cooled heat exchanger uses air as the cooling medium, and when the temperature is controlled at 35±5 degrees Celsius through the air-cooled heat exchanger, the electrolyte reduces the preheating time and improves production efficiency. The uniform heating can heat the electrolyte more evenly, avoid local excessively high or low temperatures, and ensure the uniformity and stability of the electrolysis reaction in the entire electrolytic cell. The air-cooled heat exchanger does not require additional coolant (such as water) and its circulation system, which reduces operating costs and energy consumption. It is easy to install and maintain. The structure is relatively simple and easy to install. It does not require complex piping and pump systems, and the maintenance cost is also low. Maintenance work is relatively easy to carry out. It has strong adaptability to the environment and is not limited by water resources. It can still work normally in water-scarce areas or when water supplies are unstable.
[0049] Embodiment 2:
[0050] A method for energy saving and consumption reduction of electrolytic manganese metal comprises the following steps:
[0051] S1. Insulation and heat insulation treatment of the electrolytic cell: multiple layers of insulating materials are arranged outside the electrolytic cell, and heat insulation materials are arranged outside the insulating materials. Openings are opened on the tops of the insulating materials and the heat insulation materials to allow the electrolytic cell to slide into the inside;
[0052] S2: Selecting metallic manganese: First, check whether the purity of metallic manganese meets the standard; second, observe whether the surface of metallic manganese has uniform color; third, select metallic manganese with complete particle size and shape, and then add the selected metallic manganese into the electrolytic cell;
[0053] S3: Adding additives: When adding a certain surfactant as an additive to the electrolytic copper cell, first dissolve it in deionized water to prepare a solution of a certain concentration, then add the solution to the electrolyte at a steady flow rate through evenly distributed nozzles installed on the upper part of the electrolytic cell, and observe the change in the copper deposition quality, and add additives to the inside of the electrolytic cell, the additives include selenium dioxide, sulfite ions and gelatin;
[0054] S4: Replacement of electrode materials: Before replacement, first stop the operation of the electrolytic cell and cut off the power supply, empty and clean the electrolyte in the electrolytic cell, and thoroughly clean the electrolytic cell to remove residual electrolyte and sediment, remove the old electrode and the wire, clamp or fixture connecting the old electrode, and gradually remove the old electrode. The electrode material anode includes a lead alloy anode, the cathode material includes a pure copper cathode, and the diaphragm material is an ion exchange membrane;
[0055] S5: Waste heat recovery: The electrolyte temperature is maintained at 35-45 degrees Celsius with the help of a temperature recovery device, which includes a heat pump;
[0056] S6: Controlling temperature: When controlling the temperature, the operation of the electrolytic cell is first stopped and the power supply is cut off. The first step is to detect the temperature of the electrolyte. When it exceeds 45 degrees Celsius, a temperature control device is used to cool it down. When it is lower than 30 degrees Celsius, a temperature control device is used to heat it up. When testing the temperature, the temperature control device includes an electric heater;
[0057] In S1, the insulating material is provided with multiple layers, the insulating material includes polytetrafluoroethylene PTFE, the thickness of the glass fiber reinforced plastic is 5 mm, and the thickness of the polytetrafluoroethylene PTFE is 7 mm;
[0058] The first layer is 5mm glass fiber reinforced plastic FRP, which can resist the corrosion of chemical substances in the electrolyte, maintain stable performance for a long time, and extend the service life of the equipment. In an acidic or alkaline electrolyte environment, glass fiber reinforced plastic FRP is not easily corroded. Good electrical insulation properties ensure that there will be no current leakage during the electrolysis process, improving the safety and efficiency of electrolysis. High strength and light weight have high strength and can withstand certain pressure and mechanical loads. At the same time, the weight is relatively light, which is easy to install and transport, and cost-effective. Compared with some metal materials or other high-performance engineering plastics, glass fiber reinforced plastic FRP provides good performance while having a relatively low cost;
[0059] Tetrafluoroethylene PTFE has excellent corrosion resistance and can resist the erosion of strong acids, strong alkalis and various organic solvents. Various chemical substances it comes into contact with during the electrolysis process will hardly cause damage to it. In the strongly acidic electrolytic manganese electrolyte, PTFE can remain stable and does not undergo chemical reactions. It has excellent electrical insulation properties and very high volume resistivity and surface resistivity, which can effectively prevent current leakage and ensure the safety and stability of the electrolysis process.
[0060] In S1, the thermal insulation material includes an aerogel thermal insulation material, and the thickness of the aerogel thermal insulation material is 3 mm.
[0061] Aerogel has extremely low thermal conductivity and is one of the best known thermal insulation materials. It can greatly reduce heat loss in the electrolytic cell and maintain a stable temperature environment, which helps to improve electrolysis efficiency and energy saving. Its corrosion resistance can resist the erosion of chemical substances in the electrolyte, maintain stable performance for a long time, and has high stability. Its structure is stable under high temperature and harsh environment, and it is not easy to age, deform or decompose. After using aerogel insulation materials in the experiment, the heat loss of the electrolytic cell was significantly reduced. According to statistics, a large amount of energy costs are saved every year.
[0062] In S2, firstly, the purity of the manganese metal is tested to see whether it meets the standard, secondly, the surface of the manganese metal is observed to see whether the color is uniform, thirdly, the manganese metal with complete particle size and shape is selected, and then the selected manganese metal is added into the electrolytic cell;
[0063] The purity of manganese metal is confirmed by relevant test reports or certificates. In the electrolysis process, due to the high purity of manganese metal, better and higher purity manganese metal can be electrolyzed under the same power pulse. The surface of manganese metal should be uniform in color, without obvious oxidation, rust, cracks or other defects. The smooth surface can better allow electricity to penetrate into the ore for electrolysis during the electrolysis process.
[0064] In S3, the amounts of additives are 4 parts of selenium dioxide, 3 parts of sulfite ions, and 15 parts of gelatin;
[0065] 4 parts of selenium dioxide, which can improve the structure and appearance of cathode deposits more quickly and reduce the formation of dendrites during the experiment; 3 parts of sulfite ions, which can improve the electrolysis efficiency and quality of manganese metal during the experiment; 15 parts of gelatin, which can refine crystals and make cathode deposits more uniform during the experiment;
[0066] In S4, the thickness of the electrode material is a lead alloy anode of 0.8 mm, the cathode material includes a pure copper cathode of 0.8 mm, and the thickness of the diaphragm material is an ion exchange membrane of 2.5 mm;
[0067] Lead alloy anodes at low oxygen overpotentials help reduce the overpotential of oxygen evolution and reduce energy consumption during electrolysis. While meeting the requirements of electrolysis, their comprehensive performance and cost are advantageous. Compared with some more expensive anode materials, the price of lead alloys is relatively affordable, which helps reduce production costs.
[0068] Pure copper cathode has good conductivity. Pure copper has excellent conductivity, which can ensure that the current is evenly distributed on the cathode surface, promote the effective deposition of metal manganese, and improve the electrolysis efficiency. The chemical stability is relatively stable in the electrolysis environment, and it is not easy to have excessive chemical reactions with the electrolyte, thereby reducing the loss of the cathode itself. The cost is moderate. Compared with some precious metal cathode materials, the price of pure copper is more reasonable, while ensuring the performance and controlling the cost. After the metal manganese uses pure copper cathode in the experiment, the current distribution is more uniform, and the electrolysis efficiency is increased by about 10%;
[0069] Ion exchange membranes can selectively allow specific ions to pass through. For example, when electrolyzing manganese metal, manganese ions can be allowed to pass through while preventing the migration of other impurity ions, thereby improving the purity of the electrolysis product, preventing the mixing of cathode and anode electrolytes, effectively separating the cathode and anode regions, avoiding direct mixing of cathode and anode electrolytes, ensuring that the electrolysis reaction proceeds in the expected direction, maintaining the ion concentration balance in the electrolytic cell, and making the current more concentrated for the electrolysis reaction of the target ions, thereby improving the utilization efficiency of the current, reducing energy consumption, and improving product quality. Since it can effectively prevent the migration and interference of impurity ions, it helps to obtain higher quality electrolysis products, such as purer and better crystallized manganese metal. In the experiment, after the manganese metal factory used ion exchange membranes, the impurity content in the product was significantly reduced, reaching a higher purity standard. Through the application of ion exchange membranes, the current efficiency is improved, the power consumption per unit product is reduced, and the competitiveness of the product in the market is enhanced;
[0070] In S5: the temperature control device adopts a heat exchanger or a heat pump, and when the electrolyte flows out of the tank, the temperature is absorbed and converted by the heat exchanger or the heat pump, and the electrolyte temperature is maintained at 35-40 degrees Celsius by the heat exchanger or the heat pump;
[0071] In S6: the temperature control device uses an electric heater. When the temperature of the electrolyte in the pipeline exceeds 40 degrees Celsius, the electric heater is activated. The temperature is set to 70 degrees Celsius for two minutes. When the temperature is heated to 30 degrees Celsius, the temperature of the heater is set to 40 degrees Celsius, and the temperature is waited for to rise.
[0072] The electric heater can achieve precise adjustment of the electrolyte temperature at 40 degrees Celsius, ensuring that the electrolyte is always within the optimal electrolysis temperature of 40 ± 5, thereby optimizing the rate and efficiency of the electrolytic reaction. Rapid heating can heat the electrolyte to the required temperature in a shorter time, reduce preheating time, and improve production efficiency. Uniform heating can heat the electrolyte more evenly, avoid local temperatures that are too high or too low, and ensure the uniformity and stability of the electrolytic reaction in the entire electrolytic cell. On the production line of electrolytic manganese, due to a sudden drop in outside temperature, the electrolyte temperature dropped to 35 degrees Celsius. The electric heater was started in time to raise and stabilize the temperature within the range of ± 5 of the set value of 40 degrees Celsius, avoiding the decrease in current efficiency and product quality problems caused by temperature fluctuations, increasing the power of the electric heater, achieving fine-tuning of the electrolyte temperature, and successfully improving the density and purity of manganese crystals.
[0073] Table 1
[0074]
[0075]
[0076] Among them, the temperature of the electrolyte inside the electrolytic cell is controlled by a temperature control device. By controlling the temperature of the electrolyte at 35-45 degrees Celsius, the electrolysis efficiency is 85%-90% and the impurity content is 0.05%-0.08%, and the power consumption is 100kw-120 / month. Compared with the electrolysis at 60 degrees Celsius and 20 degrees Celsius, the impurities are less than 0.1%-0.2%, and the electrolysis energy consumption is less than that at 60 degrees Celsius and the impurity content is lower than that at 20 degrees Celsius.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for energy saving and consumption reduction of electrolytic manganese metal, characterized in that: The following steps are involved: S1. Insulation and heat insulation treatment of the electrolytic cell: multiple layers of insulating materials are arranged outside the electrolytic cell, and heat insulation materials are arranged outside the insulating materials. The insulating materials and the tops of the heat insulation materials are provided with openings for the electrolytic cell to slide into the inside; S2: Selecting metallic manganese: First, check whether the purity of metallic manganese meets the standard; second, observe whether the surface of metallic manganese has uniform color; third, select metallic manganese with complete particle size and shape, and then add the selected metallic manganese into the electrolytic cell; S3: Adding additives: When adding a certain surfactant as an additive to the electrolytic copper cell, first dissolve it in deionized water to prepare a solution of a certain concentration, then add the solution to the electrolyte at a stable flow rate through evenly distributed nozzles installed on the upper part of the electrolytic cell, observe the change in the copper deposition quality, and add additives to the inside of the electrolytic cell, the additives including selenium dioxide, sulfite ions and gelatin; S4: Replacement of electrode materials: Before replacement, first stop the operation of the electrolytic cell and cut off the power supply, empty and clean the electrolyte in the electrolytic cell, and thoroughly clean the electrolytic cell to remove residual electrolyte and sediment, remove the old electrode and the wires, clamps or fixtures connected to the old electrode, and gradually remove the old electrode. The electrode material anode includes a titanium-based coated anode or a lead alloy anode, the cathode material includes a stainless steel cathode or a pure copper cathode, and the diaphragm material is an asbestos diaphragm or an ion exchange membrane; S5: Waste heat recovery: The electrolyte temperature is maintained at 35-45 degrees Celsius by means of a temperature recovery device, wherein the temperature recovery device includes a heat exchanger or a heat pump; S6: Control temperature: When controlling the temperature, first stop the operation of the electrolytic cell and cut off the power supply. The first step is to detect the temperature of the electrolyte. When it exceeds 45 degrees Celsius, a temperature control device is used to cool it down. When it is lower than 30 degrees Celsius, a temperature control device is used to heat it up. When testing the temperature, the temperature control device includes an air-cooled heat exchanger and an electric heater.
2. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: In S1, the insulating material is provided with multiple layers, and the insulating material includes ceramic or glass fiber reinforced plastic FRP, rubber or polytetrafluoroethylene PTFE, the thickness of the ceramic is 3-5mm, the thickness of the glass fiber reinforced plastic is 3-5mm, the thickness of the rubber is 5-7mm, and the thickness of the polytetrafluoroethylene PTFE is 5-7mm.
3. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: In S1, the thermal insulation material includes aluminum silicate fiber or aerogel thermal insulation material, the thickness of the aluminum silicate fiber is 3-5 mm, and the thickness of the aerogel thermal insulation material is 3-5 mm.
4. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: S2: Selecting metallic manganese: Test the purity index of metallic manganese and confirm its purity through relevant test reports or certificates. Observe the surface of metallic manganese, which should be uniform in color without obvious oxidation, rust, cracks or other defects. If there are specific requirements for particle size and shape, check whether it meets the standards.
5. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: In S3, the amounts of the additives are 2-4 parts of selenium dioxide, 1-3 parts of sulfite ions, and 5-15 parts of gelatin.
6. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: In S4, the thickness of the electrode material is 0.5-0.8mm for titanium-based coated anode or 0.5-0.8mm for lead alloy anode, the thickness of the cathode material is 0.5-0.8mm for stainless steel cathode or 0.5-0.8mm for pure copper cathode, and the thickness of the diaphragm material is 1-2mm for asbestos diaphragm or 1.5-2.5mm for ion exchange membrane.
7. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: In S5: the temperature control device uses a heat exchanger or a heat pump. When the electrolyte flows out of the tank, the temperature is absorbed and converted by the heat exchanger or the heat pump, and the electrolyte temperature is maintained at 35-40 degrees Celsius by the heat exchanger or the heat pump.
8. The method for energy saving and consumption reduction of electrolytic manganese metal according to claim 1, characterized in that: In S6: the temperature control device uses an air-cooled heat exchanger and an electric heater. When the temperature of the electrolyte in the pipeline exceeds 40 degrees Celsius, the air-cooled heat exchanger is started, with an air flow rate of 13500-27000 per minute. When the temperature of the electrolyte in the pipeline is lower than 35 degrees Celsius, the electric heater is started, and the temperature is set to 70-80 degrees Celsius for two minutes. When the temperature is heated to 20-30 degrees Celsius, the temperature of the heater is set to 40-45 degrees Celsius, and the temperature is waited for to rise.